2022
DOI: 10.3390/nu14183720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diets and Dietitians for Para-Athletes: A Pilot Study Based on Interviews

Abstract: Efforts to provide nutrition support to para-athletes have not been established to date, and are far behind those established for athletes without disabilities. In the present study, we attempted to clarify the actual situation regarding dietary challenges of para-athletes. The aim of this study was to obtain clues to effective intervention methods that encourage the practice of sports nutrition. Six active elite para-athletes (30–70 years, four males) and a female physical therapist without physical disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A study involving six athletes with lower-limb disabilities reported that the athletes did not receive regular advice from a dietitian [55]. Although nutritional knowledge was not assessed in our study, all athletes received recommendations from a sports nutritionist at least once a year.…”
Section: The Future Of Nutrition In Wheelchair Athletesmentioning
confidence: 90%
“…A study involving six athletes with lower-limb disabilities reported that the athletes did not receive regular advice from a dietitian [55]. Although nutritional knowledge was not assessed in our study, all athletes received recommendations from a sports nutritionist at least once a year.…”
Section: The Future Of Nutrition In Wheelchair Athletesmentioning
confidence: 90%
“…However, the nutritionist plays the role of trainer and educator in nutrition. He develops personalized food programs and monitors the nutritional balance of his athletes (Yokoyama et al, 2022). The nutritionist is responsible for anticipating, diagnosing and managing nutrition-related disorders.…”
Section: Nutrition Knowledge Of Subjectsmentioning
confidence: 99%